Middle term Splitting :- 4x²-5√2x+3
Answers
Answered by
5
4x² - 5√2x +3=0
⇒ 4x² -2√2x -3√2x +3 =0
⇒2√2x(√2x -1) -3(√2x -1) =0
⇒(2√2x -3)(√2x -1) =0
∴(2√2x -3) =0 or (√2x -1) =0
⇒x = 3/(2√2) or x = 1/√2
⇒ 4x² -2√2x -3√2x +3 =0
⇒2√2x(√2x -1) -3(√2x -1) =0
⇒(2√2x -3)(√2x -1) =0
∴(2√2x -3) =0 or (√2x -1) =0
⇒x = 3/(2√2) or x = 1/√2
Similar questions
History,
8 months ago
English,
8 months ago
English,
1 year ago
Math,
1 year ago
Social Sciences,
1 year ago
Social Sciences,
1 year ago
English,
1 year ago